2008
DOI: 10.1243/17403499jnn153
|View full text |Cite
|
Sign up to set email alerts
|

A review of the microstructure and rheology of carbon nanotube suspensions

Abstract: The present review is concerned with the way that the incorporation of carbon nanotubes (CNTs) into a fluid matrix can modify the microstructure and rheology of the resulting suspensions. Some background to CNT manufacture and in particular methods of dispersing them into a suspension is presented for a range of different systems, where effective dispersion of CNTs remains a delicate and open issue. Steady shear, linear viscoelasticity, non-linear viscoelasticity and extensional responses are classified for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 131 publications
(224 reference statements)
4
16
0
Order By: Relevance
“…This is in accordance with Theoretical expectations and experimental observations for fiber-reinforced composites [19][20][21][22] . The complex viscosity is also an important parameter to characterize the rheological properties of a material.…”
Section: Viscosity Of the Phenolic-cnt As A Function Of Dispersionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with Theoretical expectations and experimental observations for fiber-reinforced composites [19][20][21][22] . The complex viscosity is also an important parameter to characterize the rheological properties of a material.…”
Section: Viscosity Of the Phenolic-cnt As A Function Of Dispersionsupporting
confidence: 93%
“…(%) CNT dispersion after to be used aqueous solution and passes into the TRC. As it can be observed and has also been reported in the literature [19][20][21][22] , the storage modulus is sensible to the reinforcement resulting from the added CNTs especially in the low frequency range. Storage modulus has increased with the incorporation of the CNTs into the polymer matrix; this enhancement was significantly higher as lower frequencies.…”
Section: Viscosity Of the Phenolic-cnt As A Function Of Dispersionsupporting
confidence: 75%
See 1 more Smart Citation
“…This negatively polarizes the SWCNTs and allows them to disperse well in pure H2O without the use of additional surfactants 1 . The addition of surfactants has been shown to negatively affect the performance of CNTs and it is difficult to remove the surfactant from the CNT network after processing 14 . After acid functionalizing, the SWCNT acid mixture was diluted with de-ionized water washed through a filter to remove the acidity from the CNTs.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the indirect characterization of dispersion by other techniques (such as X-ray diffraction, rheology, infra-red analysis), or the direct measurement of relevant final features (tensile properties, electrical conductivity) are often adopted. It has been extensively shown that the rheological response of nanocomposites is sensitive to changes at different length scales (Huang et al, 2006;Lertwimolnun and Vergnes, 2006;Ray, 2006;Vermant et al, 2007;Cassagnau, 2008;Park et al, 2008;Ma et al, 2008;Vergnes, 2011). Thus, as rheometers are readily available in most laboratories, sample preparation is not too complicated and measurements are relatively straightforward, rheology is currently one of the most used methods to characterize dispersion.…”
Section: Introductionmentioning
confidence: 99%